Dental dimensions and Angle's molar classification in a group of Afro-descendants from a township of Cali, Colombia - Miguel Ángel Chaverra (2024)
Objective: To analyze the permanent teeth through mesodistal and vestibulo-palatal (vestibulo-lingual) dental diameters and Angle's molar classification to determine mean, sexual dimorphism, bilateral symmetry and population biological similarities in a group of Afro-descendants from the township of El Hormiguero, in Cali, Colombia. Materials and methods: Descriptive study that analyzed the mesodistal and vestibulo-palatal (vestibulo-lingual) diameters of permanent teeth of 36 plaster models (21 females and 15 males) of a group of Afro-descendants from the township of El Hormiguero, Cali, Colombia. Parametric and nonparametric tests were used to estimate sexual dimorphism and bilateral symmetry, in addition to correlations with Angle's molar class. A p < 0.05 was considered significant. Results: Minimal differences were found in the diameters of the right and left sides. Some lower arch teeth showed sexual dimorphism. No significant differences were observed between Angle molar class and sex, while bilateral symmetry showed a difference close to significance. The total summation of mesodistal diameters showed no relationship with Angle molar class. Conclusions: There is sexual dimorphism in the diameters in the lower arch. There was no relationship between the diameters and Angle's molar class, and there was no sexual dimorphism.